Feasibility and utility of active case finding of HIV-infected children and adolescents by provider-initiated testing and counselling: evidence from the Laquintinie hospital in Douala, Cameroon - Calixte Ida Penda; Carole Else Eboumbou Moukoko; Daniele Kedy Koum; Joseph Fokam; Cedric Anatole Zambo Meyong; Sandrine Talla; Paul Koki Ndombo (BMC, 2018)
Abstract Background Universal HIV testing and treatment of infected children remain challenging in resource-limited settings (RLS), leading to undiagnosed children/adolescents and limited access to pediatric antiretroviral therapy (ART). Our objective was to evaluate the feasibility of active cases finding of HIV-infected children/adolescents by provider-initiated testing and counseling in a health facility. Methods A cross-sectional prospective study was conducted from January through April 2016 at 6 entry-points (inpatient, outpatient, neonatology, immunization/family planning, tuberculosis, day-care units) at the Laquintinie Hospital of Douala (LHD), Cameroon. At each entry-point, following counseling with consenting parents, children/adolescents (0-19 years old) with unknown HIV status were tested using the Rapid Diagnostic Test (RDT) (Determine®) and confirmed with a second RDT (Oraquick®) according to national guidelines. For children less than 18 months, PCR was performed to confirm every positive RDT. Community health workers linked infected participants by accompanying them from the entry-point to the treatment centre for an immediate ART initiation following the « test and treat » strategy. Statistical analysis was performed, with p < 0.05 considered significant. Results Out of 3439 children seen at entry-points, 2107 had an unknown HIV status (61.3%) and HIV testing acceptance rate was 99.9% (2104). Their mean age was 2.1 (Sd = 2.96) years, with a sex ratio boy/girl of 6/5. HIV prevalence was 2.1% (44), without a significant difference between boys and girls (p = 0.081). High rates of HIV-infection were found among siblings/descendants (22.2%), TB treatment unit attendees (11.4%) and hospitalized children/adolescents (5.6%); p < 0.001. Up to 95.4% (42/44) of those infected children/adolescents were initiated on ART. Overall, 487 (23.2%) deaths were registered (122 per month) and among them, 7 (15.9%) were HIV-positive; mainly due to tuberculosis and malnutrition. Conclusion The consistent rate of unknown HIV status among children/adolescents attending health facilities, the high acceptability rates of HIV testing and linkage to ART, underscore the feasibility and utility of an active case finding model, using multiple entry-points at the health facility, in achieving the 90-90-90 targets for paediatric HIV/AIDS in RLS.